Language Use and Management in International Organizations The experience of agents of the non-profit development agency sequa gGmbH - Stobbe, Sophia (Jihočeská univerzita, 2022)
This master thesis aims to show what influence language and communication decisions have on external communication in internationally operating organizations. The research was done on the example of sequa gGmbH in Bonn, a non-profit development organization. Through interviews and observation protocols, the impressions and experiences of employees of sequa were collected.
Language Use and Management in International Organizations The experience of agents of the non-profit development agency sequa gGmbH
Keywords: language and communication decisions; intercultural communication; external communication; international organization; NGO.; language and communication decisions; intercultural communication; external communication; international organization; NGO.